2010
DOI: 10.1371/journal.pgen.1001258
|View full text |Cite
|
Sign up to set email alerts
|

A Role for ATF2 in Regulating MITF and Melanoma Development

Abstract: The transcription factor ATF2 has been shown to attenuate melanoma susceptibility to apoptosis and to promote its ability to form tumors in xenograft models. To directly assess ATF2's role in melanoma development, we crossed a mouse melanoma model (NrasQ61K::Ink4a−/−) with mice expressing a transcriptionally inactive form of ATF2 in melanocytes. In contrast to 7/21 of the NrasQ61K::Ink4a−/− mice, only 1/21 mice expressing mutant ATF2 in melanocytes developed melanoma. Gene expression profiling identified highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
63
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 61 publications
(94 reference statements)
7
63
0
Order By: Relevance
“…8 In details, Shah et al identified the same nuclear punctiform pattern shown in Figure 2 and concluded that such peculiar staining could indicate ATF2 localization in DNA repair foci following DNA damage. 35 Our results indicate that Celastrol, an active triterpene extracted by the Chinese herb "Thunder of God Vine", downmodulates ATF2-mediated transcription in a dose dependent manner (Fig. 4).…”
Section: Discussionmentioning
confidence: 61%
“…8 In details, Shah et al identified the same nuclear punctiform pattern shown in Figure 2 and concluded that such peculiar staining could indicate ATF2 localization in DNA repair foci following DNA damage. 35 Our results indicate that Celastrol, an active triterpene extracted by the Chinese herb "Thunder of God Vine", downmodulates ATF2-mediated transcription in a dose dependent manner (Fig. 4).…”
Section: Discussionmentioning
confidence: 61%
“…Neuronal-specific deletion of Atf2, mediated by nestin-driven Cre, results in embryonic cranial motor neuron degeneration, specifically in the hypoglossal, abducens and facial nuclei regions (Ackermann et al, 2011). In terms of disease models, work from our laboratory has demonstrated that the melanocyte-specific expression of a transcriptionally inactive ATF2, mediated by tyrosinase-driven Cre, is sufficient to block melanoma development in the Nras (Q61K) ::Ink4A 2/2 (Ink4A is also known as Cdkn2a) murine melanoma model (Shah et al, 2010). By contrast, expression of transcriptionally inactive ATF2 in the keratinocytes of the DMBA-TPA-induced [7,12-dimethylbenz(a)anthracene and 12-Otetradecanoylphorbol-13-acetate, respectively] murine skin cancer model increases the number and size of skin papilloma, as well as their formation rate (Bhoumik et al, 2008a).…”
Section: Regulation Of Atf2 Protein Stabilitymentioning
confidence: 99%
“…Conversely, binding of ATF2 to the histone acetyltransferase TIP49b effectively suppresses its transcriptional activity (Cho et al, 2001). ATF2-JunB dimers bind to the SOX10 promoter and suppress its transcription, with concomitant silencing of microphthalmiaassociated transcription factor (MITF) transcription in melanocytes and melanoma cells (Shah et al, 2010). In Table 1, we have categorized the known transcriptional targets of ATF2 into functional groups, along with the respective AP1 family binding partner, case-specific stimuli and cell types (see also the UCSD Signaling Gateway Molecule Pages for ATF2; http://www.…”
Section: Nuclear Functions Of Atf2mentioning
confidence: 99%
“…GLI2 appears to promote invasion and metastasis through suppression of Ecadherin expression leading to a mesenchymal-like phenotype. Also, the transcription factor ATF2 has been shown to attenuate melanoma susceptibility to apoptosis and to promote its ability to form tumors in xenografts (Bhoumik and Ronai, 2008;Shah et al, 2011). In mouse melanoma models, expression of mutant ATF2 in melanocytes strongly attenuated tumour formation.…”
Section: Future Perspectivesmentioning
confidence: 99%